Lactobacillus fermentum AGR1487 cell surface structures and supernatant increase paracellular permeability through different pathways. Issue 4 (6th May 2015) - Sengupta, Ranjita; Anderson, Rachel C.; Altermann, Eric; McNabb, Warren C.; Ganesh, Siva; Armstrong, Kelly M.; Moughan, Paul J.; Roy, Nicole C.
<x xml:space="preserve">Abstract</x> Lactobacillus fermentum is commonly found in fermented foods and is generally thought to be harmless. However, L. fermentum AGR1487 dramatically decreases transepithelial electrical resistance, a measure of intestinal barrier integrity. The results of this research show that the cell surface structure of AGR1487 is critical for its negative effect on intestinal epithelial barrier function in vitro, but also provide evidence that secreted compounds play a role. <boxed-text content-type="graphic" id="mbo3260-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>